Innovative Nanocomposites for Low Power Phase‐Change Memory: GeTe/C Multilayers. Issue 9 (3rd June 2022) - Térébénec, Damien; Bernier, Nicolas; Castellani, Niccolo; Bernard, Mathieu; Jager, Jean-Baptiste; Tomelleri, Martina; Paterson, Jessy; Cyrille, Marie-Claire; Tran, Nguyet-Phuong; Giordano, Valentina M.; Hippert, Françoise; Noé, Pierre
Abstract : Innovative nanocomposites consisting of [(GeTe)4 nm/ C1 nm ]10 multilayers (MLs) deposited by magnetron sputtering are integrated in phase‐change memory (PCM) test devices with a "wall structure." Scanning transmission electron microscopy (STEM) shows that an ML structure, with crystallized GeTe layers, is kept after integration in as‐fabricated devices and also after an additional annealing of the devices at 425 °C. The programming current (RESET current) required to reach the high resistance state of [(GeTe)4 nm /C1 nm ]10 ML devices decreases by 45% after annealing at 425 °C. The reduction in RESET current is 55% and the reduction in drift coefficient is about 40% in ML devices annealed at 425 °C compared to similar devices incorporating Ge2 Sb2 Te5 . STEM imaging, coupled with nano‐beam electron diffraction and electron energy loss spectroscopy, of ML devices in the high resistance state shows that the RESET current reduction after annealing is correlated to a reduction of the amorphized volume. Abstract : Innovative nanocomposites consisting of [(GeTe)4 nm /C1 nm ]10 multilayers integrated in phase‐change memory (PCM) devices reduce the programming current required to reach the high resistance state by 55% compared to a reference PCM device. Transmission electron microscopy imaging shows that this reduction results from improved thermal confinement in the multilayer memory cell, allowing a significant reduction in the amorphous programmed volume.